Association between Cardiac Remodeling and Metabolic Alteration in an Experimental Model of Obesity Induced by Western Diet - Ferron, Artur Junio Togneri [UNESP]; Francisqueti, Fabiane Valentini [UNESP]; Minatel, Igor Otávio [UNESP]; Silva, Carol Cristina Vágula de Almeida [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Kitawara, Koody André Hassemi [UNESP]; Garcia, Jéssica Leite [UNESP]; Corrêa, Camila Renata [UNESP]; Moreto, Fernando [UNESP]; Ferreira, Ana Lucia A [UNESP] (MDPI, 2018)
The high consumption of fat and sugar contributes to the development of obesity and co-morbidities, such as dyslipidemia, hypertension, and cardiovascular disease. The aim of this study was to evaluate the association between dyslipidemia and cardiac dysfunction induced by western diet consumption. Wistar rats were randomly divided into two experimental groups and fed ad libitum for 20 weeks with a control diet (Control, n = 12) or a high-sugar and high-fat diet (HSF, n = 12). The HSF group also received water + sucrose (25%). Evaluations included feed and caloric intake; body weight; plasma glucose; insulin; uric acid; HOMA-IR; lipid profile: [total cholesterol (T-chol), high-density lipoprotein (HDL), non-HDL Chol, triglycerides (TG)]; systolic blood pressure, and Doppler echocardiographic. Compared to the control group, animals that consumed the HSF diet presented higher weight gain, caloric intake, feed efficiency, insulin, HOMA-IR, and glucose levels, and lipid profile impairment (higher TG, T-chol, non-HDL chol and lower HDL). HSF diet was also associated with atrial-ventricular structural impairment and systolic-diastolic dysfunction. Positive correlation was also found among the following parameters: insulin versus estimated LV mass (r = 0.90, p = 0.001); non-HDL versus deceleration time (r = 0.46, p = 0.02); TG versus deceleration time (r = 0.50, p = 0.01). In summary, our results suggest cardiac remodeling lead by western diet is associated with metabolic parameters.
Keywords: cardiac remodeling; dyslipidemia; obesity